Worker/wrapper/makes it/faster - Hackett, Jennifer; Hutton, Graham (2014)
Much research in program optimization has focused on formal approaches to correctness: proving that the meaning of programs is preserved by the optimisation. Paradoxically, there has been comparatively little work on formal approaches to efficiency: proving that the performance of optimized programs is actually improved. This paper addresses this problem for a general-purpose optimization technique, the worker/wrapper transformation. In particular, we use the call-by-need variant of improvement theory to establish conditions under which the worker/wrapper transformation is formally guaranteed to preserve or improve the time performance of programs in lazy languages such as Haskell.